BETWEEN TWO WORLDS: ANALYSIZING THE CONVERGENCE OF SECULAR AND ISLAMIC LAW IN NIGERIA’S JUSTICE SYSTEM-A STUDY OF SUNDAY JACKSONS’ CASE (2015-2025) - Aristotle Isaac Jacobs; Bubarayi G. Ibani (Journal of Social Science, 2026)
Objective: This study explores the synthesis between secular and sharia law in Nigeria’s justice system: A study of Sunday Jackson’s trial of (2015-2025), it further explores how these legal traditions interact and sometimes conflict in practice. Using Jackson’s case as a focal point, it examines tensions between constitutional guarantees of human rights and religiously grounded principles, highlighting issues of jurisdictions, fairness, and legal certainty. Method: The theoretical framework for the study was discussed in an eclectic form namely: Demand-side Theory (DST), Supply-side Theory (SST) and, Legal pluralism Theory (LPT), but we adopted the later. This research employs a doctrinal and case study perspective to assess the historical development of legal pluralism, its constitutional basis, and its practical challenges. Results: It further evaluates how courts balance secular and Islamic law, especially in criminal matters, and the implications for justice delivery and human rights protection. Study findings also show that while pluralism promotes cultural and religious inclusivity, it also creates inconsistences and risks of right violations. Novelty: Nigeria’s legal system operates at the intersection of secular, customary and sharia law, creating a pluralistic framework that reflects its religious and cultural diversity. Therefore, the study recommends constitutional reforms, clearer jurisdictional boundaries, and judicial training to harmonize Nigeria’s legal systems with international human rights standards.